A service design process based on the business model CANVAS and the C-K theory - Castillo-López, Sergio (Springer, 2019)
Services are fundamental to any economy. They are responsible for most of the employment and collaborate with a substantial proportion of the Gross Domestic Product. Despite its importance, the tools and methodologies for service design in Latin America have a slow evolution. One of the reasons that explain this phenomenon is the lack of practical tools and methods to take into account the complexity of the service and the intrinsic dynamism of the design process. Another limitation of the adoption of new service design tools is a nontechnical view of the design process, situation that puts the common sense as the first resource for service design. Hence, the lack of a service design methodology avoids the learning process, the reproducibility of successful service models in a different context, and the assimilation of new design techniques. Consequently, this chapter proposes a framework to guide the conceptual design or redesign of services through the combination of the Business Model CANVAS with the C-K theory. The Business Model CANVAS is a graphical tool to represent, as simple as possible, the interaction of different elements to capture and deliver value to the market. On the other hand, the C-K theory proposes a graphical tool where Concepts (C) and Knowledge (K) interact dynamically to shape a process, without increasing complexity. The integration offers a design framework useful to deal with the challenging context of service development. A case study illustrates this practical approach.